Impact on Customer Perception towards ATM Services Provided By the Banks Today: A Conceptual Study (International Journal of Scientific Research and Management (IJSRM), 2018)
ATM is one of the most popular delivery channel as it permits customers to do Anywhere, Anytime banking. Both, the bank and customers stand to gain in several ways. While ATMs bring down the cost per transaction, increase efficiency by reducing workload of staff, they help to increase accuracy, speed, save time, money and efforts of customers. Thus, ATM impacts the customer services and leads to better customer satisfaction. The banking system is facing challenges with stiff competition and advancement of technology. It becomes imperative for service providers to meet or exceed the target customers’ satisfaction with quality of services expected by them. This paper explores the significant dimensions of ATM (automatic teller machine) service quality and its effect on customer satisfaction.